HELP project - a dreamed-of multiwavelength dataset for SED fitting: The influence of used models for the main physical properties of galaxies. Issue Volume 15:Issue S341(2019) (November 2019) - Małek, Katarzyna; Buat, Veronique; Burgarella, Denis; Roehlly, Yannick; Shirley, Raphael; ,
Abstract: The Herschel Extragalactic Legacy Project (HELP) focuses to publish an astronomical multiwavelength catalogue of millions of objects over 1300 deg 2 of the Herschel Space Observatory survey fields. Millions of galaxies with ultraviolet–far infrared photometry make HELP a perfect sample for testing spectral energy distribution fitting models, and to prepare tools for next-generation data. In the frame of HELP collaboration we estimated the main physical properties of all galaxies from the HELP database and we checked a new procedure to select peculiar galaxies from large galaxy sample and we investigated the influence of used modules for stellar mass estimation.